Arahan Pengembangan sebagai Upaya Peningkatan Kawasan Pariwisata Pantai Modangan Kabupaten Malang - Mey Putri Andini; Nunung Nuring Hayati; Rindang Alfiah (Jurnal Ilmiah Membangun Desa dan Pertanian, 2024)
Modangan Beach is an administrative beach located in Donomulyo District, Malang Regency, East Java Province. It has potential as a tourist destination because it is included in the provincial tourism strategic area. The beach is famous for its paragliding attraction. Apart from the potential of Modangan Beach, there are several problems, including the lack of optimal infrastructure and promotional facilities that should support tourism activities at Modangan Beach. Therefore, a development direction is needed in the Modangan Beach tourism area. This research aims to determine the priority of development of the Modangan Beach area and the direction of development of the Modangan Beach area. The research method used to answer the first problem was the Analytical Hierarchy Process (AHP) technique to determine the development priorities of the Modangan Beach tourism area. The second method uses Triangulation analysis to identify the direction of management in accord with the prioritized development of the Modangan Beach tourism area that has been identified. The research outcome is to determine the development priorities that must be carried out at Modangan Beach, namely improving road access followed by toilets, clean water networks, beach conditions, and management offices. Then, the proper development direction will be provided after the triangulation analysis. The development direction is the improvement and rearrangement of the road to the beach tourism area to facilitate tourist accessibility, the presence of cleaners and cleaning tools to keep the toilet conditions clean, water distribution from PDAM to the beach tourism area, maintenance, and optimization of tourism potential, conducting tourism promotions, adding a management office, involving the surrounding community for area management.